Selected areas of female MPs presence in the Polish Sejm in 1991–2018 – quantitative aspects - Pająk-Patkowska, Beata (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The article analyzes representation of women in the Polish Parliament (Sejm) in 1991–2018, a period which corresponds to 8 terms of office. The analysis excludes the Sejm of the 10th term of office (1989–1991) due to the specific nature of the election and a different mode of its operation in the period concerned. Areas of activity and female MP participation were defined based on documents that regulate the working of the Sejm. The hypothesis assumes that main bodies and institutions of the legislative branch (Presidium, Marshal, parliamentary committees) show a disparity between the number of male and female MPs. Another hypothesis is that women are more active in committees that deal with issues stereotypically associated with women, such education and health. The study involved document and statistical analyses to compare data pertaining to the activity of male and female MPs. Research materials comprise data available at sejm.gov.pl (archives of eight terms of office). It is worth emphasizing that the website is a reliable source of information. A large part of resources has been digitized which facilitates access to research materials.

Celem artykułu jest analiza aktywności kobiet w polskim Sejmie w okresie pomiędzy 1991 a 2018 rokiem, co obejmuje 8 kadencji. Z analiz wyłączono działalność Sejmu X kadencji (1989–1991), ze względu na specyfikę wyborów, jak i odmienny sposób funkcjonowania sejmu w tym okresie. W oparciu o dokumenty regulujące pracę Sejmu, określone zostały możliwe pola aktywności w tym organie oraz udział w nich kobiet. Przyjęto hipotezę zakładającą, że w organach władzy czy miejscach gwarantujących do niej większy dostęp (Prezydium Sejmu, pełnienie funkcji Marszałka Sejmu, przewodniczenie komisjom sejmowym) występuje dysproporcja pomiędzy posłami i posłankami. Założono również, że kobiety są bardziej aktywne w tych komisjach, które zajmują się obszarami stereotypowo przypisywanymi kobietom, takimi jak edukacja czy zdrowie. Zastosowano metodę analizy dokumentów oraz metodę statystyczną w celu porównania danych dotyczących aktywności posłów i posłanek. Materiał badawczy stanowiły dane dostępne na stronie sejm.gov.pl (archiwum ośmiu kadencji). Warto podkreślić, że strona ta stanowi wiarygodne źródło danych, wiele zasobów zostało już zdygitalizowanych, co znacznie ułatwia dostęp do materiału badawczego.
Wybrane obszary aktywności kobiet w Sejmie RP w latach 1991-2018 – aspekt ilościowy
Keywords: women in politics; political activity of women; Sejm; women in the Sejm; parliamentary committees; kobiety w polityce; aktywność polityczna kobiet; Sejm; kobiety w Sejmie; komisje sejmowe